Speciation of Gram-positive bacteria in fresh and ambient-stored sub-tropical marine fish - Al Bulushi, I.; Poole, S.; Barlow, R.; Deeth, H.; Dykes, Gary (Elsevier, 2010)
This study identified Gram-positive bacteria in three sub-tropical marine fish species; Pseudocaranx dentex (silver trevally), Pagrus auratus (snapper) and Mugil cephalus (sea mullet). It further elucidated the role played by fish habitat, fish body part and ambient storage on the composition of the Gram-positive bacteria. A total of 266 isolates of Gram-positive bacteria were identified by conventional biochemical methods, VITEK, PCR using genus- and species-specific primers and/or 16S rRNA gene sequencing. The isolates were found to fall into 13 genera and 30 species. In fresh fish, Staphylococcus epidermidis and Micrococcus luteus were the most frequent isolates. After ambient storage, S. epidermidis, S. xylosus and Bacillus megaterium were no longer present whereas S. warneri, B. sphaericus, Brevibacillus borstelensis, Enterococcus faecium and Streptococcus uberis increased in frequency. Micrococcus luteus and S. warneri were the most prevalent isolates from P. dentex, while E. faecium and Strep. uberis were the most frequent isolates from P. auratus and M. cephalus. With respect to different parts of the fish body, E. faecium, Strep. uberis and B. sphaericus were the most frequent isolates from the muscles, E. faecium, Strep. uberis from the gills and M. luteus from the gut. This study showed a diversity of Gram-positive bacteria in sub-tropical marine fish; however, their abundance was affected by fish habitat, fish body part and ambient storage. © 2009 Elsevier B.V. All rights reserved.